Re-thinking Ibn ‘Arabī's Status as Mujtahid - Arnel, Iskandar; Valiyyul Haqq, Muhammad (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
Ibn 'Arabī, who is also referred to as Doctor Maximus (al-Shaykh al-Akbar) within the Sufi world, has been recognized for centuries as one of the awliyā' of God. Nevertheless, this status did not preclude numerous scholars from designating him as a mujtahid. The issue lies in the conception of a walī as an individual endowed with spiritual knowledge that enables them to comprehend matters without the necessity of learning or research. This prompts further inquiry into the question of whether Ibn 'Arabī, the walī, can be designated a mujtahid. This article employs a qualitative approach and a review of the extant literature to examine the claims of scholars who are based on Ibn 'Arabī's own thoughts. The culmination of the research indicated that, on the one hand, Ibn 'Arabī asserted that a walī cannot be designated as a mujtahid, as his autonomous determination is derived from the method of kashf. Therefore, it can be posited that the individual in question is not, in fact, Ibn 'Arabī. Nevertheless, historical evidence suggests that Ibn 'Arabī engaged in rigorous study of Islamic law and jurisprudence. This suggests the possibility that he may have utilized ijtihād in his independent decision-making, thereby classifying him as a mujtahid. However, prior to conducting a thorough investigation into the underlying factors that influenced Ibn 'Arabī's independent decisions, it would be premature to categorize him as a mujtahid